1968
DOI: 10.1111/j.1432-1033.1968.tb00342.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Properties of the 12alpha-Hydroxylase in Cholic Acid Biosynthesis. Bile Acids and Steroids 198

Abstract: The 12a-hydroxylation of the steroid nucleus in cholic acid biosynthesis was studied in the microsomal fraction of rat liver homogenate. The reaction was shown to require NADPH. A participation of flavins in the 12a-hydroxylase system or a requirement for metal ions could not be shown. Carbon monoxide inhibited partly the 12a-hydroxylase system. The effect of some inhibitors of steroid hydroxylations was tested and the influence of sex and age was studied. The relative rates of 12a-hydroxylation of a number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

1968
1968
1996
1996

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…The reaction is catalyzed by the microsomal fraction fortified with NADPH (15,37). The conversion of 5-cholestene-3{1,7a-diol into 5-cholestene-3{1, 7a, l2a-triol, which is a reaction in another pathway for the formation of 5{1-cholestane-3a,7a,12a-triol, is also catalyzed by the microsomal fraction fortified with NADPH (30,37), as is the 12a-hydroxylation of 5{1-cholestane-3a,7a-diol and 7a-hydroxy-5{1-cholestan-3-one (37). The rates of 12a-hydroxylation of these C27-steroids differ considerably: the rate with 5-cholestene-3{1,7a-diol is about one-tenth and with 5{1-cholestane-3a,7a-diol about half of that with 7a-hydroxy-4-cholesten-3-one (37).…”
Section: A-hydroxylationmentioning
confidence: 99%
“…The reaction is catalyzed by the microsomal fraction fortified with NADPH (15,37). The conversion of 5-cholestene-3{1,7a-diol into 5-cholestene-3{1, 7a, l2a-triol, which is a reaction in another pathway for the formation of 5{1-cholestane-3a,7a,12a-triol, is also catalyzed by the microsomal fraction fortified with NADPH (30,37), as is the 12a-hydroxylation of 5{1-cholestane-3a,7a-diol and 7a-hydroxy-5{1-cholestan-3-one (37). The rates of 12a-hydroxylation of these C27-steroids differ considerably: the rate with 5-cholestene-3{1,7a-diol is about one-tenth and with 5{1-cholestane-3a,7a-diol about half of that with 7a-hydroxy-4-cholesten-3-one (37).…”
Section: A-hydroxylationmentioning
confidence: 99%
“…Rabbit liver lacks such a 7a-hydroxylating system and since 12a-hydroxy-5/3-cholestan-3-one and 5/3-cholestane-3a,l2a-diol were not metabolized to cholic acid in the bile fistula rabbit, it can be concluded that rat liver as well as rabbit liver are not able to 7a-hydroxylate 12a-hydroxy-5/3-cholestan-3-one and 5~-cholestane-3a,l2a-diol to any significant extent. When 12a-hydroxycholest-4-en-3-one and cholest-5-ene-3~,12a-diol [5] were administered to bile fistula rabbits about 3 and loo/,, respectively, of the metabolites formed could be accounted for as cholic acid. These data agree with the results of the experiments with rat liver homogenates.…”
Section: Discussionmentioning
confidence: 99%
“…Another pathway for the formation of 7a,l2a-dihydroxycholest-4-en-3-one has been described involving the 12a-hydroxylation of 7 whydroxycholest-4-en-3-one catalyzed by the microsomal fraction fortified with NADPH [ 2 ] . Recently, some properties of the 12a-hydroxylase system were reported including measurements of the rate of 12a-hydroxylation of a number of C,,-steroids [3]. The rate of 12a-hydroxylation of 7a-hydroxycholest-4-en-3-one was found to be about ten times faster than Note.…”
mentioning
confidence: 99%
“…Low sensitivity of the 12~-hydroxylase system towards carbon monoxide has been observed with microsomal fraction and crude reconstituted systems [2,[4][5][6]101. However, the sensitivity was higher -up to 80 inhibition-with purified cytochroine P-450 LM4 from starved rabbits.…”
Section: Discussionmentioning
confidence: 99%